2014
DOI: 10.1210/en.2014-1466
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Oxytocin Treatment of Obese Diabetic Mice on Adiposity and Diabetes

Abstract: Oxytocin has been suggested as a novel therapeutic against obesity, because it induces weight loss and improves glucose tolerance in diet-induced obese rodents. A recent clinical pilot study confirmed the oxytocin-induced weight-reducing effect in obese nondiabetic subjects. Nevertheless, the mechanisms involved and the impact on the main comorbidity associated with obesity, type 2 diabetes, are unknown. Lean and ob/ob mice (model of obesity, hyperinsulinemia, and diabetes) were treated for 2 weeks with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
148
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(156 citation statements)
references
References 37 publications
8
148
0
Order By: Relevance
“…In addition, chronic central or systemic oxytocin increases epididymal white adipose tissue expression of hormone sensitive lipase (a key mediator of adipocyte lipolysis) (1, 23) while reducing expression of fatty acid synthase (an enzyme linked to lipogenesis) in rats (1). While it remains to be determined whether chronic CNS infusions of oxytocin increase circulating levels (23) in sufficient concentrations to trigger a peripheral effect on lipolysis, it is possible that these effects in our model may be attributed, in part, to a direct effect on adipocytes (60,83,94) where OTRs are expressed (1,31,32,60,83,94,101) or an indirect mechanism. The mechanism underlying these effects may involve outgoing polysynaptic sympathetic nervous system projections from PVN oxytocin neurons to both inguinal (86) and epididymal white adipose tissue (86,89).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, chronic central or systemic oxytocin increases epididymal white adipose tissue expression of hormone sensitive lipase (a key mediator of adipocyte lipolysis) (1, 23) while reducing expression of fatty acid synthase (an enzyme linked to lipogenesis) in rats (1). While it remains to be determined whether chronic CNS infusions of oxytocin increase circulating levels (23) in sufficient concentrations to trigger a peripheral effect on lipolysis, it is possible that these effects in our model may be attributed, in part, to a direct effect on adipocytes (60,83,94) where OTRs are expressed (1,31,32,60,83,94,101) or an indirect mechanism. The mechanism underlying these effects may involve outgoing polysynaptic sympathetic nervous system projections from PVN oxytocin neurons to both inguinal (86) and epididymal white adipose tissue (86,89).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, existing pharmacotherapeutic strategies to treat obesity are relatively ineffective and there is widespread need for improved treatments. We and others have previously shown that chronic systemic administration of oxytocin elicits weight loss or reductions of weight gain in DIO and genetically obese rodent models, DIO nonhuman primates, and obese humans through mechanisms that include reduction of food intake (1,10,23,49,53,59,104,105), increased energy expenditure (10), increases in lipolysis (1,8,23), and/or reductions in RQ (23,49,53). (23,49,53).…”
Section: Perspectives and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Nasal treatment of oxytocin was also reported to decrease food intake in both mice and humans [24,35,36]. However, this reduction of BW is not only induced by food intake reduction; oxytocin also induces lipolysis in adipose tissue and decreases fat mass [29,34,[37][38][39][40]. Recent studies have clarified the various new mechanisms of oxytocin's anorexigenic effects through the CNS and promotion of catabolic reactions on peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Animals developed obesity when they were deficient of OT or OT receptors [15] [16]. Peripheral OT treatment reduced adipose tissue proportion and also ameliorated food intake, fatty liver, as well as glucose intolerance in ob/ob mice [17] [18] [19]. Adipocyte size was smaller after treating with OT, the lipogenic related genes fatty acid binding protein 4 (FABP4), peroxisomal proliferator activated receptor gamma (PPARγ), glucose transporter 4 (GLUT4), and leptin mRNA levels in adipose tissues were increased in rats, indicating that OT treatment improves nutrient provision in adipose tissue [20].…”
mentioning
confidence: 99%